2023
DOI: 10.3389/fncel.2023.1276506
|View full text |Cite
|
Sign up to set email alerts
|

The origins and dynamic changes of C3- and S100A10-positive reactive astrocytes after spinal cord injury

Qing Zhao,
Yi-long Ren,
Yan-jing Zhu
et al.

Abstract: Accaumulating studies focus on the effects of C3-positive A1-like phenotypes and S100A10-positive A2-like phenotypes of reactive astrocytes on spinal cord injury (SCI), however the origins and dynamic changes of C3- and S100A10-positive reactive astrocytes after SCI remain poorly understood. Through transgenic mice and lineage tracing, we aimed to determine the origins of C3- and S100A10-positive reactive astrocytes. Meanwhile, the distribution and dynamic changes in C3- and S100A10-positive reactive astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Similar results were obtained in the study by Ying et al, 2022, where it was found that training on a water treadmill promotes the development of S100A10 + -reactive astrocytes [25]. This same study also demonstrated a reduction in pro-inflammatory astrocytes (the second line of astrocytes, known as resident cells [55][56][57][58]) expressing the C3 protein. The existing discrepancy between the observed levels of C3 mRNA in our work and the C3 protein in Ying et al, 2022 [25] may be due to differential regulation of translation, post-translational modifications, protein half-life, and antibody epitope availability.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were obtained in the study by Ying et al, 2022, where it was found that training on a water treadmill promotes the development of S100A10 + -reactive astrocytes [25]. This same study also demonstrated a reduction in pro-inflammatory astrocytes (the second line of astrocytes, known as resident cells [55][56][57][58]) expressing the C3 protein. The existing discrepancy between the observed levels of C3 mRNA in our work and the C3 protein in Ying et al, 2022 [25] may be due to differential regulation of translation, post-translational modifications, protein half-life, and antibody epitope availability.…”
Section: Discussionsupporting
confidence: 84%
“…The reduction in the number of GFAP + /ALDH1L1 + -astrocytes in the group with controlled training in our study also supports the hypothesis of a positive effect of physical exercise on the state of the glial scar. Recent studies have demonstrated that the microenvironment of the glial scar gradually transforms, inhibiting regeneration as the scar matures, and the function of astrocytes progressively shifts from stimulating to inhibiting axonal regeneration [55,56]. Limiting secondary damage caused by inflammation may be a specific function of astrocytes, precursors of ependymal cells (one of the three astrocyte lineages identified in SCI [55][56][57][58]), including S100A10 + -reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation